Van Batavia naar Weltevreden; Het Bataviaasch Genootschap van Kunsten en Wetenschappan, 1778-1867 - Groot, Hans (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2009)
The Batavian Society of Arts and Sciences (Bataviaasch Genootschap van Kunsten en Wetenschappen), was founded in 1778 to become the predecessor of the National Library and National Museum of the Republik Indonesia. It was considered to be the most important cultural and scholarly organization of the Netherlands East Indies in the time of the Dutch East India Company (VOC) and the colonial period. This studie pays attention to the foundation, programme and area of interest of the Society, also to its members, organization, growth, decline and resurrection, but most of all to the relation with the government of a formally private enterprise, that sometimes seemed to become part of the governmental structure. The archives of the Society are kept in the National Archives of the Republik Indonesia. Since 1878, they have only scarcely been available to scholars from outside of the Society. They have, however, proven to be of great importance to historians, linguists, and anthropologists.